Readiness of Regular Teachers for the Inclusion of Learners with Special Education Needs - Oliver C. Logroño; Jeanette T. Gongora (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to determine the level of readiness of regular teachers for the inclusion of learners with special education needs. The researcher used total population sampling to determine the study respondents. This study used the descriptive-survey method. Regular teachers were asked about their readiness to include learners with special education needs through a questionnaire with age, gender, years of teaching, and attendance at seminars as moderator variables. There were 140 items in the questionnaire and 20 items per parameter. The statistical treatment used in the study were mean and SD. The study showed that regular teachers in the Loreto district were highly prepared for inclusive education. As a result of the study, AIM, which stands for Alliance in Inclusion Movement, was developed and proposed to assist regular teachers in improving their readiness level to include learners with special education needs. Pre-service and in-service training about inclusive education was highly recommended for regular teachers. A thorough program on monitoring and evaluation by the National and Division DepEd Officials must be conducted to examine the practice of inclusive education in the country, especially in areas with no SPED Center.